Intra oral reconstruction with buccal fat pad: Recent applications of autologous tissue transplantation as a local flap - Khaleque Hasibul; Fumi Nakai; Yasuhiro Nakai; Ayako Jinzenji; Akinori Iwasaki; Takaaki Ogawa; Yumiko Ohbayashi; Minoru Miyake (JPRAS Open, 2016)
Intra oral reconstruction with buccal fat pad (BFP) is an identical procedure during reconstructive head and neck surgery. It has a successful outcome in restoring both soft and hard tissues for more than 3 decades. The purpose of this study was to represent a series of cases and review of the recent diversified application of BFP in intra-oral region during reconstruction. The Authors are presenting 12 cases (Male – 8/66.7%; Female – 4/33.33%, mean age – 66.33 years) of BFP reconstruction from small to medium sized defect in oral cavity. The diameter of the BFP graft was between 10 mm and 55 mm. Only one case was restored in mandible while others were in maxillary region. All patients were recovered within a short time. The yellow fat tissues were turned into reddish color within 1 week. Patient recovered with almost normal mucosa before 4th week. BFP reconstruction had considered as a quick and easy to restore flap during most intra-oral reconstruction. Rapid healing without any complications added additional advantage. High blood supply and easy access make it as a first consideration. We also evaluated the merits, demerits, distance between host and donor site, size of defect and site of reconstruction.